Demand estimation with infrequent purchases and small market sizes - Ali Hortaçsu; Olivia R. Natan; Hayden Parsley; Timothy Schwieg; Kevin R. Williams (Quantitative Economics, 2023)
We propose a demand estimation method that allows for a large number of zerosale observations, rich unobserved heterogeneity, and endogenous prices. We do so by modeling small market sizes through Poisson arrivals. Each of these arriving consumers solves a standard discrete choice problem. We present a Bayesian IV estimation approach that addresses sampling error in product shares and scales well to rich data environments. The data requirements are traditional market-level data as well as a measure of market sizes or consumer arrivals. After presenting simulation studies, we demonstrate the method in an empirical application of air travel demand.
Keywords: C11; C18; L93; 330; Discrete choice modeling; demand estimation; zero-sale observations; Bayesian methods; airline markets